Análisis de la implementación de las metodologías BIM en los procesos de construcción en las obras de vivienda Villa Sofía y bodegas San Francisco en el departamento de Santander (2021)
This document analyzes the benefits and advantages of the implementation of the BIM methodology in the design and network processes in a home in the municipality of Malaga, Santander, based on the internship process at the ESCO company, through an analysis quantitative and qualitative. First, the collection of information was carried out through research and also through surveys of personnel who have experience in construction processes, sharing their knowledge and obtaining a greater focus on research, then the comparison of CAD methodologies with BIM was carried out. , demonstrating the benefits and advantages of BIM, with fewer errors in the designs, more speed and effectiveness, where several professionals work on the same model, finally a model of a multi-family home was made, to further strengthen the knowledge about of the use of the software, allowing to be updated in the construction industry and to be more competent in the market